2001
DOI: 10.1097/00002030-200108170-00014
|View full text |Cite
|
Sign up to set email alerts
|

`Chemical condoms’ for the prevention of HIV infection: evaluation of novel agents against SHIV89.6PDin vitro and in vivo

Abstract: D2S and PRO-2000, novel inhibitors of HIV entry, showed evidence of protection in vivo, comparable to that seen with the virucide, N9. These data, together with the results of phase I and phase II studies in healthy women which have shown minimal toxicity, support plans for a phase III efficacy trial of chemically simple inhibitors of HIV entry with low toxicity, for the prevention of HIV infection in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 18 publications
0
46
0
2
Order By: Relevance
“…Bourne et al (1999) reported on the topical microbicide PRO 2000, a naphthalene sulfonate polymer, which protects mice against genital herpes infection. The results of a study in macaques suggested that the HIV entry inhibitors dextrin-2-sulfate and PRO 2000 protects against Simian HIV vaginal challenge (Weber et al, 2001). In clinical Phase I and Phase II studies dextrin sulfate gel and PRO 2000 gel formulations were found to be well tolerated, with promising local and systemic safety (Stafford et al, 1997, Van Damme et al, 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Bourne et al (1999) reported on the topical microbicide PRO 2000, a naphthalene sulfonate polymer, which protects mice against genital herpes infection. The results of a study in macaques suggested that the HIV entry inhibitors dextrin-2-sulfate and PRO 2000 protects against Simian HIV vaginal challenge (Weber et al, 2001). In clinical Phase I and Phase II studies dextrin sulfate gel and PRO 2000 gel formulations were found to be well tolerated, with promising local and systemic safety (Stafford et al, 1997, Van Damme et al, 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Microbicides are designed to inhibit virus infection by directly inactivating the virus or interrupting its attachment, entry, or replication [177] . Recent insights into how HIV infiltrates the genital mucosa, initial interactions with immune cells and the role of dendritic cells in transporting the virus to the lymph nodes have suggested numerous potential new targets for microbicides [178,179] .…”
Section: Antimicrobial and Antibacterial Agentsmentioning
confidence: 99%
“…Macaque challenge experiments provided some data supporting the efficacy of DS gel (15). Two of four rhesus macaques pretreated with vaginally administered DS gel at a concentration of 1% were uninfected following vaginal challenge with SHIV 89.6 pd (10 4 TCID in 0.87 mL given twice 3 hours apart).…”
mentioning
confidence: 94%
“…It is a potent inhibitor of the growth of diverse laboratory strains of HIV-1 in a variety of human cell lines and peripheral blood lymphocytes (13,14), with inhibition of 50% of virus at 2-6 g/mL, as determined by established assays. It has a high selectivity index and is nontoxic in cell culture (15). Although DS has marked anticoagulant activity (16), its large average molecular weight of 20 kd makes systemic absorption across the vaginal mucosa unlikely.…”
mentioning
confidence: 99%